PERSEPSI SISWA TERHADAP PEMBELAJARAN DARING MATA PELAJARAN SENI BUDAYA MATERI SENI RUPA KELAS VII DI SMP NEGERI 12 PADANG - Yola Permata Syahri; Yusron Wikarya (Universitas Negeri Padang, 2021)
The purpose of this study was to find out students' perception of online learning of Art and Culture subjects of Fine Arts Class VII at SMP Negeri 12 Padang. This research method uses a type of descriptive quantitative research. Data collection techniques in this study use questionnaire instruments and data analysis techniques using descriptive statistics with percentages. The population in this study amounted to 295 students of Grade VII SMP Negeri 12 Padang using Simple Random Sampling technique so as to determine the number of samples 20% of the total number of students is 61 students of Grade VII SMP Negeri 12 Padang. Based on the results of the overall research, it was concluded that students' perception of online learning of Art and Culture subjects in Fine Arts Class VII at SMP Negeri 12 Padang with a perception criteria score of 1.46. So it can be said that the perception of Grade VII students towards online learning in the category is very lacking.Keywords: perception, online learning, fine arts